2007
DOI: 10.1302/0301-620x.89b7.18983
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte apoptosis in the regenerated articular cartilage after allogenic chondrocyte transplantation in the rabbit knee

Abstract: We attempted to repair full-thickness defects in the articular cartilage of the trochlear groove of the femur in 30 rabbit knee joints using allogenic cultured chondrocytes embedded in a collagen gel. The repaired tissues were examined at 2, 4, 8, 12 and 24 weeks after operation using histological and histochemical methods. The articular defect filling index measurement was derived from safranin-O stained sections. Apoptotic cellular fractions were derived from analysis of apoptosis in situ using TUNEL stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This method allowed us to examine cartilage specimens histologically for identification and quantification of TUNEL-positive cells in situ, which represent apoptotic cell death in the tissue [10,30]. After a 24-hour treatment with various solutions (Table 1), sections were stained following the manufacturer's instructions.…”
Section: Combination Of Steroids and Local Anestheticsmentioning
confidence: 99%
“…This method allowed us to examine cartilage specimens histologically for identification and quantification of TUNEL-positive cells in situ, which represent apoptotic cell death in the tissue [10,30]. After a 24-hour treatment with various solutions (Table 1), sections were stained following the manufacturer's instructions.…”
Section: Combination Of Steroids and Local Anestheticsmentioning
confidence: 99%
“…[6,7] Despite the huge potential, limitations exist with respect to culture and clinical domains, and we attempt to provide an account of the same [Table 1], with potential solutions to tackle them. Various important studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18] conducted to highlight the…”
Section: Overview Of Allogeneic Chondrocyte Implantationmentioning
confidence: 99%
“…Pro‐inflammatory cytokines and pro‐apoptotic factors may be induced by local inflammation and also by the processing and storage of the cells and tissues prior to implantation [146]. It has been demonstrated that some chondrocytes used in chondrocyte transplantation undergo apoptosis [147], which may be due to a unique process known as chondroptosis. Therefore, the modulation of factors that interfere with this process may be of relevance to cartilage repair.…”
Section: Interference Of Inflammation With Cartilage Repairmentioning
confidence: 99%